Pelatihan Strategi Social Media Marketing Untuk Pemberdayaan Umkm Masyarakat Rt 29 Kelurahan Sawah Lebar Baru - Rehan Andreas Saputra; Anisa Purwanti; Tarrya Dewi Anastacia; Kartika Dewi Arizin; Shofitri Elma Raihani; Lydia Gustina Putri (Universitas Dehasen Bengkulu, 2026)
The community of RT 29, Sawah Lebar Baru Village, Ratu Agung District, Bengkulu City, holds great potential for developing Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary and craft sectors. However, most entrepreneurs still rely on conventional marketing methods, limiting market reach. The objective of this community service (PkM) activity is to enhance the digital competence of MSME actors in RT 29 through intensive social media marketing training. The implementation method used a Participatory Action Research (PAR) approach, including needs assessment, face-to-face training (focusing on Instagram Business and WhatsApp Business), and practical assistance. The activity involved 25 participants, consisting of housewives and MSME owners. Evaluation results showed an average knowledge increase of 45% regarding content creation techniques and business account optimization. Furthermore, 80% of participants successfully applied this knowledge by creating new business accounts and publishing at least five product contents, which led to an increase in inquiries and initial sales. This program is recommended as an intervention model to encourage the digitalization of MSMEs at the village level.